Optimizing controlled-release urea and urea combinations for sustainable rice-wheat production under nitrogen reduction - Yu Tao; Yu Tao; Yu Tao; Dehai Zhang; Dehai Zhang; Dehai Zhang; Zhipeng Xing; Zhipeng Xing; Zhipeng Xing; Zhipeng Xing; Chuan Ni; Chuan Ni; et al. (Frontiers in Plant Science)
Excessive nitrogen fertilization poses a threat to agricultural sustainability. Achieving high crop yield while improving soil health under reduced nitrogen (N) input is a global concern. This two-year rice-wheat rotation study was designed with two N fertilizer levels (conventional N level and reduced N level) and four controlled-release urea (CRU) application modes, along with a control CK (farmer’s conventional fertilization mode). Effects on yield, nitrogen use efficiency (NUE), and soil fertility were compared. Polymer-coated urea (PCU) was employed as the CRU material in this study. Significantly lower annual yields were observed under sole PCU. The PCU + U treatments increased yields by 9.16–15.00% over CK. The highest rice-wheat yield and nitrogen recovery efficiency occurred with 40% PCU + 30% U basal fertilizer + 30% U panicle fertilizer application mode. Nitrogen reduction decreased yield and plant nitrogen but improved nitrogen recovery efficiency. However, the RN-PCU + U mode achieved yields comparable to CK. RN-PCU + U treatments provided stable yields and higher economic benefits, with the latter increasing by 6.3-35.7% compared to CK. Soil nutrient content varied significantly among PCU application modes. The RN 70% PCU + 30% U basal fertilizer showed the best performance on soil fertility: organic matter content was 2.9% higher than CK, and total nitrogen was 9.3% higher than CK after two rice-wheat rotations. Panicle fertilizer enhanced nutrient uptake and reduced residual soil nutrient levels. Correlation analysis indicated that increased plant N and soil available phosphorus were associated with higher yields, whereas elevated soil alkali-hydrolyzed N content promoted organic matter accumulation. PCU + U application can compensate for the decrease of rice-wheat yield under nitrogen reduction and improve the activity of soil nutrients. Our results suggest that the 70% PCU + 30% U basal application mode optimizes nitrogen efficiency, sustains rice-wheat yields, and enhances soil fertility under reduced nitrogen input. These findings could inform future sustainable agricultural practices designed to reduce nitrogen use while maintaining crop yield.